Relationship between the individual facets of job, job satisfaction and organisational commitment - Lahai, Moses M. R.; Md. Sail, Rahim; Muhamad, Mazanah; Suandi, Turiman (Universiti Putra Malaysia Press, 2004)
Numerous studies have documented positive relationships between overall job satisfaction and organisational commitment. Some research has, however, focused on the individual facets of job that constitute the overall job satisfaction. The study's design involved a survey of workers in a variety of electrical and electronic industries in the Klang Valley in Malaysia. The responses of a total sample of 426 operators were submitted to a series of Pearson Product Moment Correlation and multiple regression analysis in order to test the hypotheses. As hypothesized the results provided evidence to support that satisfaction with the individual facets or dimensions of job satisfaction (Herzberg's Job satisfaction model) were all positively related to organisational commitment. Multiple regression analysis supported the hypothesised relationships between five variables in Herzberg's model and organisational commitment. Overall, both the intrinsic (motivational) factors and the extrinsic (hygiene) factors of Herzberg's model were found to have relevance and practical implications for predicting organisational commitment.